Pengaruh Kepuasan Kerja terhadap Kinerja Karyawan melalui Komitmen Afektif pada PT Cipta Nirmala - Widya Ningsih, Lia (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to explain and identify job satisfaction, affective commitment and employee performance at PT Cipta Nirmala. The position of affective commitment in mediating job satisfaction on PT Cipta Nirmala's employee performance was tested and analyzed in this study. The population is all permanent employees in the PT Cipta Nirmala office section, amounting to 50 employees. The analysis technique uses SEM analysis by Smart PLS3. This research gives the result that positively and significantly, job satisfaction affects employee performance. Positively and significantly, job satisfaction is affected by affective commitment. There is no mediating affective commitment to job satisfaction in influencing employee performance.